Linear relationships between shoot magnesium and calcium concentrations among angiosperm species are associated with cell wall chemistry - White, Philip J.; Broadley, Martin R.; El-Serehy, Hamed A.; George, Timothy S.; Neugebauer, Konrad (Oxford Journals, 2018)
Background Linear relationships are commonly observed between shoot magnesium ([Mg]shoot) and shoot calcium ([Ca]shoot) concentrations among angiosperm species growing in the same environment.